The Safety and Efficiency of Tirofiban in Acute Ischemic Stroke Patients Treated with Mechanical Thrombectomy: A Multicenter Retrospective Cohort Study. (1st May 2020) - Zhao, Lili; Jian, Yating; Li, Tao; Wang, Heying; Lei, Zhang; Sun, Man; Li, Ye; Zhang, Yiheng; Dang, Meijuan; Huqing, Wang; Hong, Sun; Ru, Zhang; et al.
Abstract : Introduction . Limited comparative studies have reported the safety and efficacy of tirofiban in acute ischemic stroke (AIS) patients after mechanical thrombectomy (MT). Additionally, the available studies are inconsistent with each other, which makes application of tirofiban unclear in neuro-intervention. Here, we performed a comparative retrospective study to investigate whether tirofiban combined with MT improves short- and long-term prognosis in AIS patients and whether its use is associated with complications. Method . Retrospective data were collected for AIS patients admitted between January 2013 and January 2019 at three stroke centers. According to whether tirofiban was used during the operation, patients were divided into tirofiban group and control group. Multivariate and COX regression analyses were performed to determine the association of tirofiban treatment with safety and efficiency in subjects treated with MT. Result . A total of 174 patients were analyzed, of whom 89 (51.1%) were treated with tirofiban. There were no differences in the incidence of symptomatic intracerebral hemorrhage (10.2% vs. 10.6%, p = 0.918 ), parenchymal hemorrhage type 2 (18.0% vs . 16.5%, p = 0.793 ), and reocclusion at 24 h (3.4% vs . 10.6%, p = 0.060 ) between the tirofiban group and control group. Multivariate regression showed that tirofiban was not associated with intracerebral hemorrhage, early neurological deterioration, neurological improvement at 7 days, functional independence at 3-month and 9-month follow-up, or death at 9-month follow-up (adjusted p > 0.05 for all). However, AIS patients treated with MT + tirofiban showed a trend towards acquiring faster functional independence, with a median time to acquire functional independence of 4.0 months compared with 6.5 months in the control group (risk ratio = 1.49, 95% confidence interval 0.98–2.27; long rank p = 0.066 ). Conclusion . Tirofiban may help AIS patients given MT to gain functional independence faster, without increasing the risk of complications.